Separation of Crystal Violet Dye from Wastewaters by Using Supported Liquid Membrane Technology - M. Waqar Ashraf; Michael P. Collins; M. Amin Mir; Abdus Salam; Anwar Ul-Hamid (Journal of Chemistry)
The current study enumerates the use of supported liquid membrane (SLM) technology to remove and recover crystal violet dye from wastewaters. The management of textile industry waste effluents is one of the main concerns of environmental health experts due to having excessive concentrations of dyes and resistance to biodegradation. Liquid membranes offer an affordable and green method for the selective removal of dyes from aqueous solutions. To create a liquid membrane, refined and edible vegetable oils were supported on microporous polymeric films of polypropylene (PP1E). Various parameters influencing transport, such as pH range in the feed solution, initial dye concentration, acid concentration in the strip solution, oil viscosities, and membrane lifetime, have been studied. The maximum flux value (1.7×10−5 mg/cm2/s) for crystal violet dye was obtained with sunflower oil-supported membrane at a pH of 12 in the feed solution and a concentration of 0.3 M hydrochloric acid in the strip solution. Under ideal conditions, the maximum amount of dye was transported within 6 hours. Studies on membrane stability and morphology revealed that the flux remained constant up to about 24 hours and then decreased gradually. Morphological studies showed that this may be attributed to deformation of pores shape and gradual clogging.